Drug-facilitated Crimes: A Review of the Spectrum of Drugs Involved in Drug-facilitated Crimes - Rashmi Sharma; Vinny Sharma (Indian Journal of Forensic Medicine and Pathology, 2025)
Drugs can alter a victim’s perception and decision-making. Drug-facilitated crimes (DFCs) include drug-facilitated sexual assault (DFSA), robbery, murder, and drug trafficking. These drugs are typically disguised in alcoholic and non-alcoholic beverages and food and the majority of the cases included powerful central nervous system depressants. Drugs utilised in sexual assaults are frequently distributed at raves, dance clubs, and bars, but they are also being promoted at private gatherings. Pharmaceutical drugs, including benzodiazepines and their derivatives (such as zolpidem, zopiclone, or zaleplon), are implicated in over 60% of cases of DFC. Among these drugs, clonazepam (26%), zolpidem (16%), bromazepam (15%), histamine antagonists (8.2%), neuroleptics (3.9%), and anesthetics (specifically GHB and ketamine, which collectively account for 2.8% of the cases) are commonly employed in DFCS. This article aims to offer a comprehensive examination of the substances frequently employed to facilitate criminal behavior, together with an exploration of their underlying mechanisms of action.